(untitled) (Research, Society and Development, 2022)
Objective: to analyze, through the literature, the perception of intensive care nurses related to pain management and assessment. Methods: This is a narrative review of the literature, carried out in LILACS, MEDLINE and BDENF databases, based on studies published between 2010 and 2020. Results: The perception of nurses about pain management and assessment is inadequate. However, resident or newly graduated nurses have a higher perception than professionals who have been outside educational institutions for a longer time, that is, we observe that nurses who work in care do not take professional qualification courses and do not participate in permanent and continuing education programs. Thus, there is a need to develop strategies to train these professionals, through investment in training, institution of care protocols for the efficient care of critically ill patients who show episodes of pain. Conclusion: the scarcity of recent studies, in the last 3 years, made it impossible to interrelate data to match the perception of these professionals in a comprehensive way.